Permukiman Liar (Squatter Settlement) Di Jalur Kereta Api Kota Semarang - Mohammad Agung Ridlo (Jurnal Planologi, 2020)
AbstraCtSquatter settlement is increasingly spreading in various urban corners of Indonesia, including in Semarang Metropolitan City. The reality of existing squatter settlements invaded vacant land, unpreserved and lacked (no) supervision from landowners, eventually forming slum enclaves, one of which was on the railway line in Semarang City. Railways should not be allowed to be used as residential areas. The squatter settlement is inhabited by people on low incomes (economically incapable). Research methods are conducted in a qualitative scriptive way, through empirical observation, interactively, with inductive methods. The approach of the room system is carried out to interpret circum citizen activity related to the request or zoning.Meanwhile, theoretical studies were conducted to help identify and analyze in this study. This research illustrates that squatter settlement occurs in addition to the retardation and poverty experienced by citizens, also due to the inability of the government and its apparatus in terms of supervision (Uncontrolled). Therefore, space arrangement is required (including planning, coaching, implementation, supervision and control).Keywords: squatter settlement, railway AbstrakSquatter settlement makin merebak di berbagai sudut perkotaan di Indonesia, termasuk di Kota Semarang Metropolitan. Realita yang ada squatter settlement merebak menginvasi lahan-lahan kosong, tidak terpelihara dan kurang (tidak ada) pengawasan dari pemilik lahan,  akhirnya membentuk enclave-enclave kumuh, salah satunya di jalur kereta api di Kota Semarang. Jalur kereta api semestinya tidak diperkenankan untuk dijadikan sebagai kawasan permukiman. Squatter settlement tersebut dihuni oleh orang-orang yang berpenghasilan rendah (tidak mampu secara ekonomi). Metode Penelitian dilakukan secara diskriptif kualitatif,  melalui observasi empirik, interaktif, dengan metoda induktif. Pendekatan sistem keruangan dilakukan untuk menginterpretasikan circum aktivitas warga kaitannya dengan permintakatan atau zoningnya. Sedangkan kajian teoritis dilakukan untuk membantu mengidentifikasi dan menganalisis dalam penelitian ini. Penelitian ini menggambarkan bahwa squatter settlement terjadi selain masih adanya keterbelakangan dan kemiskinan yang dialami oleh warga, juga dikarenakan ketidakmampuan pemerintah dan aparatnya dalam dalam hal pengawasan (Uncontrolled). Karenanya, diperlukan adanya penataan ruang (meliputi perencanaan, pembinaan, pelaksanaan, pengawasan dan pengendalian).Kata Kunci: squatter settlement, jalur kereta api